2014
DOI: 10.1073/pnas.1411548112
|View full text |Cite
|
Sign up to set email alerts
|

Protein design algorithms predict viable resistance to an experimental antifolate

Abstract: Methods to accurately predict potential drug target mutations in response to early-stage leads could drive the design of more resilient first generation drug candidates. In this study, a structurebased protein design algorithm (K* in the OSPREY suite) was used to prospectively identify single-nucleotide polymorphisms that confer resistance to an experimental inhibitor effective against dihydrofolate reductase (DHFR) from Staphylococcus aureus. Four of the top-ranked mutations in DHFR were found to be catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 27 publications
2
72
0
Order By: Relevance
“…For example, Meiler and co-workers [76] recently showed that MSD resulted in better agreement with observed evolutionary sequence profiles of antibodies when compared with single state design. In another example [5, 6], Anderson, Donald and co-workers used MSD to predict active site mutations in a drug target that confer resistance to a drug while maintaining the natural function of the enzyme.…”
Section: Algorithms For Multistate Protein Designmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Meiler and co-workers [76] recently showed that MSD resulted in better agreement with observed evolutionary sequence profiles of antibodies when compared with single state design. In another example [5, 6], Anderson, Donald and co-workers used MSD to predict active site mutations in a drug target that confer resistance to a drug while maintaining the natural function of the enzyme.…”
Section: Algorithms For Multistate Protein Designmentioning
confidence: 99%
“…The first stage is selecting a target tertiary/quaternary protein fold that will be designed for a specific function. Often the selected fold is one that performs a similar function and can later be redesigned to a new one [5–9]. In other cases, a protein that has a completely different function is used as a scaffold and repurposed for a new one [1012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multistate design is particularly challenging when designing positively for some criteria but negatively against others (33), requiring that the goals be treated separately instead of simply combined into a single goal. A variety of algorithmic approaches, based on explicit structural modeling (34-37), sequence potentials derived from the evolutionary record (15), and sequence potentials derived from structural modeling (38), have driven applications such as modifying protein interaction specificity (39)(40)(41), designing peptide inhibitors (42)(43)(44), altering substrate specificity (45)(46)(47), characterizing resistance mechanisms (48), and enabling a single protein to adopt multiple folds (49). We have focused on a Pareto optimization framework (50) as the basis for elucidating and explicitly optimizing trade-offs between criteria and thereby providing the recently well-discussed advantages of provable optimality guarantees, such as enabling more direct interpretation of experimental data according to the driving models without concern for algorithmic bias or sampling failure (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several protein design algorithms have successfully predicted protein sequences that fold and bind the desired target in vitro (Frey et al, 2010;Roberts et al, 2012;Rudicell et al, 2014;Stevens et al, 2006;Georgiev et al, 2012;Georgiev and Donald, 2007;Georgiev et al, 2014;Donald, 2011), and even in vivo (Reeve et al, 2015;Roberts et al, 2012;Rudicell et al, 2014;Georgiev et al, 2012;Georgiev et al, 2014;Donald, 2011). However, protein design is NP-hard (Kingsford et al, 2005), making algorithms that guarantee optimality expensive for larger designs where many residues are allowed to mutate simultaneously.…”
Section: Introductionmentioning
confidence: 99%